The Rio 2016 Olympics: Analyzing rule 40`s moment to shine - Grady, J. (Sport Marketing Quarterly, 2016)
The International Olympic Committee (IOC) sent shock waves through the Olympic advertising and sponsorship community when it announced in February 2015 that it was relaxing Rule 40 of the Olympic Charter to allow generic (non-Olympic themed) advertising featuring athletes during the Rio 2016 Games (Mackay, 2015). According to the IOC, the purpose of the Rule is to preserve the unique nature of the Games by preventing over-commercialization and to keep the focus on the athletes` performance (International Olympic Committee, n.d.). Notably, while the IOC does not expressly reference ambush marketing in stating its purpose, preserving the Olympics` "sources of funding" is cited (International Olympic Committee, n.d.), referring to Rule 40`s critical role in protecting long-standing global partners whose sponsorship dollars fund the Games (Mackay, 2015).